2021
DOI: 10.1002/1878-0261.12962
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of small cell carcinomas of the uterine cervix

Abstract: Small cell carcinoma (SCC) of the uterine cervix is a rare and aggressive form of neuroendocrine carcinoma, which resembles small cell lung cancer (SCLC) in its histology and poor survival rate.Here we sought to define the genetic underpinning of SCCs of the uterine cervix and compare their mutational profiles with those of human papillomavirus (HPV)-positive head and neck squamous cell carcinomas, HPV-positive cervical carcinomas and SCLCs using publicly available data. Using a combination of whole-exome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 75 publications
1
23
1
Order By: Relevance
“…Similarly, a study by Cho et al described recurring mutations in ATRX, EBRR4, and AKT/mTOR pathway genes in the pathogenesis of small-cell cervical NEC [ 44 ]. Schultheis et al characterized genomes and discovered highly recurring Tp53 and Rb1 alterations in lung NEC and p53 and RB tumor suppressor protein inactivation in cervical NEC, indicating small-cell NECs are convergent phenotypes [ 45 ].…”
Section: Cervical Nenmentioning
confidence: 99%
“…Similarly, a study by Cho et al described recurring mutations in ATRX, EBRR4, and AKT/mTOR pathway genes in the pathogenesis of small-cell cervical NEC [ 44 ]. Schultheis et al characterized genomes and discovered highly recurring Tp53 and Rb1 alterations in lung NEC and p53 and RB tumor suppressor protein inactivation in cervical NEC, indicating small-cell NECs are convergent phenotypes [ 45 ].…”
Section: Cervical Nenmentioning
confidence: 99%
“…In addition to changes in staging and treatment of cervical cancers over time, SCNCC is now recognized as an HPV-driven cancer ( Schultheis et al, 2022 ). With our historical cohort, we did not have adequate data to determine associations with HPV status and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To compare whether the profile of somatic mutations affecting cancer-related genes in this CS-related EC harboring a germline PTEN mutation would be distinct from that of sporadic ECs with somatic PTEN mutations, we performed hierarchical cluster analysis, which groups tumors based on their similarity in mutation profiles. Using the CS-related EC described here and 77 sporadic PTEN-mutant ECs of CN-L molecular subtype from TCGA [23] and a curated set of 505 cancerrelated genes [27], we found that the CS-related EC intermingled with the sporadic PTEN-mutant ECs rather than forming a separate branch/ cluster (Fig. 3D).…”
Section: Molecular Features and Mutational Signatures Analysis Of Pten-mutant Ecsmentioning
confidence: 94%
“…Both the EC and OC occurring in this CS patient share the same copy number gains and losses, including a 1q gain. D, Hierarchical cluster analysis of somatic mutations identified in 505 cancer-related genes [27] using complete linkage and Euclidian distance metric, including the CS patient's EC from this study (Cowden_EC), which harbors a PTEN germline mutation and is of CN-L molecular subtype, and 77 sporadic PTEN-mutant ECs of CN-L molecular subtype from The Cancer Genome Atlas [23]. This CS-related EC intermingles with the sporadic PTEN-mutant ECs, rather than forming a distinct cluster, suggesting that their somatic mutational profiles are similar.…”
Section: Case Resolutionmentioning
confidence: 99%